2012
DOI: 10.1097/qad.0b013e32834ed814
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and loss to follow-up in the first year of ART

Abstract: Objectives To analyse mortality, loss to follow-up (LTFU) and retention on antiretroviral treatment (ART) in the first year of ART across all age-groups in the Malawi national ART programme. Design Cohort study including all patients who started ART in Malawi’s public sector clinics between 2004 and 2007. Methods ART registers were photographed, information entered into a database and merged with data from clinics with electronic records. Rates per 100 patient-years and cumulative incidence of retention we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
57
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 33 publications
(39 reference statements)
10
57
3
Order By: Relevance
“…Eighty-five percent of youth in our study population were female, on par with the sex distribution observed among adolescents and young adults in other studies in Africa [11,13,19,20]. In our study, 19% of female youth were pregnant at enrollment into HIV care, and 20% enrolled through PMTCT, highlighting an important point of entry into clinical care for this population.…”
Section: Discussionsupporting
confidence: 78%
“…Eighty-five percent of youth in our study population were female, on par with the sex distribution observed among adolescents and young adults in other studies in Africa [11,13,19,20]. In our study, 19% of female youth were pregnant at enrollment into HIV care, and 20% enrolled through PMTCT, highlighting an important point of entry into clinical care for this population.…”
Section: Discussionsupporting
confidence: 78%
“…We chose to censor follow-up time at ART initiation, in order to report clinical event risks among untreated children. Alternative approaches, such as competing-risk analysis, 37,38 would permit creation of survival curves and partial adjustment of clinical event risks for the impact of ART initiation over follow-up periods expanded to include time on ART, but would not permit an analysis focused only on events among children prior to ART initiation. These data thus provide an estimate of HIV disease progression in the current ART era, but prior to universal access to ART for HIV-infected infants.…”
Section: Discussionmentioning
confidence: 99%
“…[20][22] Reports describing clinical outcomes in this age group have documented significant challenges, with numerous studies noting high rates of loss to follow-up and early mortality. [23][28] Many factors—including late presentation, malnutrition, lack of caregiver involvement, nondisclosure, and HIV-related stigma—contribute to these findings. [27], [29], [30] Whether the quality of care received by children and young adults is associated with loss to follow-up or mortality has not been assessed.…”
Section: Introductionmentioning
confidence: 99%